Categorization by humans and machines - Nakamura, Glenn V.; Medin, Douglas L.; Taraban, Roman (Psychology of learning and motivation, 1993)
The objective of the series has always been to provide a forum in which leading contributors to an area can write about significant bodies of research in which they are involved. The operating procedure has been to invite contributions from interesting, active investigators, and then allow them essentially free rein to present their perspectives on important research problems. The result of such invitations over the past two decades has been collections of papers which consist of thoughtful integrations providing an overview of a particular scientific problem. The series has an excellent tradi.